Non-destructive testing of train axle using ultrasonic phased arrays - Labayen, Rosario Rafael Joel (Nanyang Technological University, 2021)
Over the recent years, there is a growing demand for railroad transportation. It has become an essential part of life in Singapore. Singapore has continuously expanded the transport system on this little, small island. The rise in demand has resulted in the need for shorter and accurate inspection intervals of important train parts such as the train axle. The failure of an axle can lead to the potential derailment of the train. Train derailment may result in serious damages such as loss of lives, properties, and large repair costs. The main objective of this research is to explore and develop an automated ultrasonic inspection technique to prevent such failures. One of the most used techniques in the industry is Phased Array Ultrasonic Testing (PAUT). In this project, the focus has been on the application of PAUT of train axles and the development of a PAUT device with automation capabilities. The device for PAUT automation has been machined and subjected to a series of experiments. Experiments have used PAUT techniques to identify target defects on the train axle where the effectiveness of the device will be validated. It is critical that the research and development of more advanced PAUT techniques continue. This is to further the technological advancement in the railroad transportation industry and all industries where Non-Destructive Testing is applied. As the demand continues to grow, it is important to ensure that safety is always a priority.